Employee Engagement and Spiritual Leadership in Private Higher Education in South Africa - Kumalo, Sibongiseni; Schutte, Flip (International Review of Management and Marketing, 2024)
Tough competition for talent forces companies to find ways to keep employees engaged. Disengaged workers cost businesses billions and hurt their ability to hire and retain top performers. This problem is also present in higher education. This study critically assesses the relationship between spiritual leadership and employee engagement. The research uses a positivist paradigm. The research employs a deductive approach with a correlational design and a survey strategy to investigate this reality. The target population is full-time employees in private higher education institutions in Gauteng, South Africa. A random sample of 220 out of the estimated population of 1621 was chosen. Data was collected through a questionnaire. The study found a positive linear relationship between spiritual leadership and employee engagement. To this extent, spiritual leadership principles influence employee engagement. This study recommends that organisations provide appropriate conditions informed by spiritual leadership principles. This will encourage employees to display their due role performance and engage accordingly.